2014
DOI: 10.1007/s13204-014-0341-2
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using marine algae Caulerpa racemosa and their antibacterial activity against some human pathogens

Abstract: We present the synthesis and antibacterial activity of silver nanoparticles using Caulerpa racemosa, a marine algae. Fresh C. racemosa was collected from the Gulf of Mannar, Southeast coast of India. The seaweed extract was used for the synthesis of AgNO 3 at room temperature. UV-visible spectrometry study revealed surface plasmon resonance at 413 nm. The characterization of silver nanoparticle was carried out using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(107 citation statements)
references
References 35 publications
8
86
0
1
Order By: Relevance
“…The following functional groups were identified such as aromatic primary amine (C-N stretch), secondary amine N-H bend, organic nitrates, carbonate ions and aliphatic fluoro compounds C-F stretch. The IR bands at *1709.83 and 1369 cm -1 are characteristic of C-O and C-O stretching modes, respectively, of the carboxylic group (Kathiraven et al 2015). The strong band at *1037 cm -1 arises from C-O-C and C-OH vibrations (Solomun et al 2004;Ankamwar et al 2005;Huang et al 2007;Kannan and Abraham John 2008).…”
Section: Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
“…The following functional groups were identified such as aromatic primary amine (C-N stretch), secondary amine N-H bend, organic nitrates, carbonate ions and aliphatic fluoro compounds C-F stretch. The IR bands at *1709.83 and 1369 cm -1 are characteristic of C-O and C-O stretching modes, respectively, of the carboxylic group (Kathiraven et al 2015). The strong band at *1037 cm -1 arises from C-O-C and C-OH vibrations (Solomun et al 2004;Ankamwar et al 2005;Huang et al 2007;Kannan and Abraham John 2008).…”
Section: Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
“…Our previous report demonstrated that silver nanoparticles can successfully be synthesized in a facile and cost-effective way using leaf extracts of Piper nigrum (Augustine et al 2014e). Biosynthesized silver nanoparticles were reported for their excellent antibacterial activity against wide range of microorganisms (Gnanadesigan et al 2012;Kathiraven et al 2014;Netala et al 2014;Sinha et al 2014;Kumar et al 2015;Kokila et al 2015;Roy et al 2014). Antifungal activity of biosynthesized silver nanoparticles is also well studied (Kumar et al 2013;Medda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So, eco-friendly and Phyto-friendly bio-originated silver Nanoparticles may negotiate the toxic effect of chemical originated Silver Nanoparticles. Some seaweeds had been reported as raw material for green synthesis of Silver Nanoparticles such as Caulerpa racemosa [5] Turbinaria conoides [6] and some seaweed synthesized silver Nanoparticles were evaluated for their potential for seed germination [7][8][9][10][11][12] which reported that seaweed synthesized Silver Nanoparticles was Phyto-friendly and had promoting effect on seed germination but it was promoting the seeds germination in compare to normal water and also seaweed extract and seaweed liquid bio-fertilizer. Silver Nanoparticles was also reported for their application in medicine to reduce the infection in burn treatment and prevent the adherence of dental bacterial colonization [13,14].…”
Section: Introductionmentioning
confidence: 99%